Developing Interactive Android-Based E-Learning Media as a Virtual Laboratory for the Students of Office Administration Education - Andi Basuki; Ummi Saiful Ummah (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2020)
The industrial revolution 4.0 leads to an increase in job competition. It should eventually be prepared with personal competence, especially for students in the Department of Office Administration Education. The study aims to develop an interactive e-learning media as a virtual laboratory on a meeting organization course. This study aimed to examine the eligibility of the media and to know the response of the students. This study applied a research and development (R & D) model which developed by Borg and Gall. This virtual laboratory is designed with some attractive features such as (1) meeting schedule, (2) start the meeting, (3) meeting minutes, (4) content sharing, (5) chat, (6) meeting materials, (7) record the meeting, (8) and contact. The current research product is E-Learning media, an interactive virtual laboratory worth applying in the learning activities developed by the researchers. It is made based on the validation of the experts and the positive response of the students.